Red mud geopolymer stabilized homogeneously dense mixture and design method

CN122977762APending Publication Date: 2026-10-27CHANGAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610951580.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

本发明通过激发工业固废赤泥、粉煤灰和矿渣粉的胶凝活性,所制备的赤泥基地聚合物胶凝材料28天抗压强度为35.8MPa,可完全替代高能耗、高污染的水泥材料,且具有早强高强的特点。本发明通过人造轻集料替代天然集料以缓解资源压力,摆脱传统道路基层材料对天然集料的依赖,推动道路基层材料向全再生化转变。本发明通过赤泥基地聚合物和人造轻集料的体系化设计,可规模化无害化消纳赤泥,消除赤泥堆存导致的土壤盐碱化与重金属污染风险,同时赤泥作为零成本原料,可降低传统水泥稳定碎石混合料的建设成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977762A_ABST
    Figure CN122977762A_ABST
Patent Text Reader

Abstract

The present application belongs to the field of industrial solid waste resource utilization, and particularly relates to a kind of red mud geopolymer stable uniform compact type mixture and design method.According to mass fraction, it includes: natural aggregate 78~91 parts, artificial light aggregate 9~22 parts, red mud geopolymer 9~15 parts;The present application stimulates the cementing activity of industrial solid waste red mud, fly ash and slag powder, and the prepared red mud geopolymer cementing material has a 28-day compressive strength of 35.8MPa, which can completely replace high energy consumption, high pollution cement materials, and has the characteristics of early strength and high strength.The present application can scale up the harmless disposal of red mud through the systematic design of red mud geopolymer and artificial light aggregate, eliminate the risk of soil salinization and heavy metal pollution caused by red mud storage, and at the same time, as a zero-cost raw material, it can reduce the construction cost of traditional cement stabilized gravel mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of industrial solid waste resource utilization, specifically relating to a stable, uniform, and dense mixture of red mud and geopolymer and its design method. Background Technology

[0002] With the deepening of the national "dual-carbon strategy," the high energy consumption, high carbon emissions, and non-renewable resources of traditional road base materials are becoming increasingly prominent. Cement, as the core cementitious material in road base mixtures, accounts for 7% to 8% of the nation's total industrial energy consumption in its production, and its direct CO2 emissions account for 12% of the nation's total CO2 emissions. Meanwhile, the over-exploitation of natural aggregates not only damages the ecological environment, but its price continues to rise due to resource scarcity, further increasing engineering costs. Against this backdrop, developing low-carbon, environmentally friendly, and sustainable new road base materials has become crucial to solving the environmental problems associated with traditional materials.

[0003] Red mud, a highly alkaline solid waste generated from the alumina industry, has accumulated to over 4 billion tons globally. This massive accumulation not only occupies land but also severely pollutes soil and groundwater. In recent years, geopolymer technology has provided a new path for the high-value utilization of red mud. By activating the silica-alumina phase components in red mud with alkaline activators, low-carbon cementitious materials can be prepared, exhibiting early strength, corrosion resistance, and low shrinkage. Simultaneously, the silica-alumina components abundant in red mud are similar to the raw material components of traditional artificial lightweight aggregates, possessing the potential for reaction with artificial lightweight aggregates. Currently, the application of artificial lightweight aggregates is mostly limited to building insulation, lacking synergistic design with geopolymer cementitious materials. Furthermore, current red mud geopolymer-stabilized crushed stone mixture base courses often directly apply the strength design standards of cement-stabilized crushed stone. Differences in material properties mean that existing strength standards cannot ensure that the designed materials achieve optimal pavement structural performance.

[0004] Therefore, if red mud-based polymers can be combined with artificial lightweight aggregates to completely replace cement and natural aggregates, and strength design standards that conform to the material properties can be established, not only can industrial solid waste red mud be disposed of, but also the resource and environmental contradictions existing in traditional cement-based materials can be resolved, and the transformation of road engineering towards green and sustainable development can be promoted.

[0005] In view of this, the present invention is hereby proposed. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a stable, uniform, and dense mixture of red mud geopolymer and its design method.

[0007] To achieve the above objectives, the present invention provides the following technical solution: On the one hand, the present invention provides a stable, uniform and dense mixture of red mud geopolymer, which, by mass parts, comprises: 78-91 parts of natural aggregate, 9-22 parts of artificial lightweight aggregate, and 9-15 parts of red mud geopolymer; The artificial lightweight aggregate, by weight, includes: 60-70 parts red mud, 12-16 parts slag, 1-3 parts fly ash, 2-4 parts activator powder, and 16-23 parts water. The red mud geopolymer comprises, by weight parts: 52-62 parts red mud, 42-52 parts slag, 8-12 parts fly ash, 12-16 parts activator powder, and 40-50 parts water.

[0008] Specifically, the different particle sizes of the natural aggregate and the artificial lightweight aggregate are proportioned as follows by mass percentage: 9-22% for artificial lightweight aggregate (5-10mm), 32-48% for natural aggregate (5-10mm), 15-16% for natural aggregate (3-5mm), and 28-30% for natural aggregate (0-3mm).

[0009] Specifically, the artificial lightweight aggregate has the following technical standards: water absorption rate of 8.8~10.0% and bulk density of 1003~1043 kg / m³. 3 The compressive strength of the cylinder is 7.31~8.51MPa.

[0010] Specifically, the red mud geopolymer has the following characteristics: initial setting time of 3.8~4.1h, final setting time of 6.2~6.6h, and 28-day compressive strength of 35.8~36.3MPa.

[0011] Secondly, the present invention provides a design method for a red mud geopolymer-stabilized, uniform, and dense mixture as described above, the design steps of which are as follows: S1. Weigh out the geopolymer powder, alkali activator powder and water according to the mass composition, prepare the alkali activator solution, mix the geopolymer powder and add the alkali activator and stir evenly, extrude and mold, sieve, and then allow to stand at room temperature for hydration and subsequent curing in a curing box to obtain artificial lightweight aggregate. S2. Weigh out the geopolymer powder, alkali activator powder and water according to the mass composition, prepare the alkali activator solution, mix the geopolymer powder and add the alkali activator, and then stir at low and high speeds until uniform to obtain the red mud geopolymer. S3. Weigh the artificial lightweight aggregate, natural crushed stone and red mud geopolymer according to the mass composition, mix the artificial lightweight aggregate, natural crushed stone and red mud geopolymer evenly to obtain a stable, uniform and dense red mud geopolymer mixture.

[0012] Specifically, in S3, the relationship between the mass fractions of the artificial lightweight aggregate and the red mud geopolymer is determined as follows: S31. Conduct compaction tests on red mud geopolymer-stabilized, uniform, and dense mixtures to determine the maximum dry density ρ under different amounts of artificial lightweight aggregate and geopolymer content. ij With optimum moisture content w ij Maximum dry density refers to the maximum dry mass density that the mixture can achieve after adjusting the moisture content under a specified compaction work; optimum moisture content refers to the moisture content at which the mixture can achieve maximum dry density during the compaction process. Maximum dry density and optimum moisture content are usually determined by compaction test: For a certain mix ratio, several different moisture content levels are set, and after mixing, they are compacted in layers according to the specified compaction work. The wet density and actual moisture content of each group of specimens are measured and converted to obtain the corresponding dry density. Then, a compaction curve is plotted with moisture content on the x-axis and dry density on the y-axis. As the moisture content increases, the dry density usually increases first and then decreases. The dry density corresponding to the peak of the curve is the maximum dry density under that mix ratio, and the moisture content corresponding to the peak point is the optimum moisture content.

[0013] S32, at the maximum dry density ρ ij With optimum moisture content w ij Under these conditions, cylindrical specimens are formed and cured to the specified age. The 7-day unconfined compressive strength and 7-day splitting strength are tested to determine the geopolymer content and artificial lightweight aggregate content of the red mud geopolymer stable, uniform, and dense mixture that meet the strength standard requirements.

[0014] Specifically, in S32, the steps for determining the 7d unconfined compressive strength and the 7d splitting strength are as follows: S321. The pavement structure and calculation conditions are proposed. The elastic modulus of the red mud geopolymer stable uniform dense base course under different working conditions is adopted by formula (1). in, denoted as t, where 4183 is the elastic modulus of the base material at age t, and 4183 is the empirical coefficient obtained from regression fitting. For the fitting formula, t represents the age; stress calculation software was used to calculate the tensile stress at the bottom of the red mud geopolymer stable uniform dense base course under different working conditions. ; S322. Assuming the flexural tensile strength [s] of the red mud polymer-stabilized uniform and dense base course, the fatigue damage of the red mud polymer-stabilized uniform and dense base course under different working conditions is calculated using formula (2). D p Then, the cumulative fatigue damage D is calculated using formula (3); Among them, D pFor the first p Fatigue damage values ​​under various working conditions; n p For the first p The actual number of times it is used under various working conditions For the first p The number of fatigue cycles that a material can withstand under a certain working condition usually refers to the number of times the vehicle load or axle load is applied under that working condition. S323. When the cumulative fatigue damage is 0.95~1.0, [s] is accepted as the flexural strength standard; otherwise, [s] is adjusted and step 3.2 is repeated until the cumulative fatigue damage meets the requirements. S324. Calculate the 7d flexural strength standard [s7] using formula (4) from [s]. Wherein, 0.82 is the reference strength coefficient, which is usually obtained by experimental fitting; To fit the empirical formula; S325. Using formula (5), calculate the 7d splitting strength standard [R] from [s7]. t ], using formula (6) from [R t Calculate the standard 7-day unconfined compressive strength [R] c ]: .

[0015] Specifically, in S32, the mass percentages of the geopolymer content and the artificial lightweight aggregate content are as follows; When the mass content of the artificial lightweight aggregate is 9-13%, the mass content of the red mud geopolymer is 9-11%, and the remainder is natural aggregate; When the mass content of the artificial lightweight aggregate is 13-17%, the mass content of the red mud geopolymer is 11-13%, and the remainder is natural aggregate; When the mass content of the artificial lightweight aggregate is 17-22%, the mass content of the red mud geopolymer is 13-15%, and the remainder is natural aggregate.

[0016] Thirdly, the present invention provides an application of the red mud geopolymer-stabilized, uniform, and dense mixture as described above, or the red mud geopolymer-stabilized, uniform, and dense mixture prepared by the design method described above, in road engineering.

[0017] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects: This invention, by stimulating the cementitious activity of industrial solid waste red mud, fly ash, and slag powder, produces a red mud-based polymer cementitious material with a 28-day compressive strength of 35.8 MPa. This material can completely replace high-energy-consuming and high-polluting cement materials and exhibits early strength and high strength characteristics. This invention alleviates resource pressure by replacing natural aggregates with artificial lightweight aggregates, eliminating the dependence of traditional road base materials on natural aggregates and promoting the transformation of road base materials towards full recycling. Through the systematic design of red mud-based polymers and artificial lightweight aggregates, this invention enables the large-scale, harmless disposal of red mud, eliminating the risks of soil salinization and heavy metal pollution caused by red mud stockpiling. Simultaneously, red mud, as a zero-cost raw material, can reduce the construction cost of traditional cement-stabilized crushed stone mixtures. Attached Figure Description

[0018] The accompanying drawings are incorporated in and form part of this specification, and together with the description serve to explain the principles of the invention.

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, those skilled in the art can obtain other drawings based on these drawings without creative effort.

[0020] Figure 1 This is a design flowchart for the present invention. Detailed Implementation

[0021] Exemplary embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Rather, they are merely examples consistent with some aspects of the invention as detailed in the appended claims.

[0022] To enable those skilled in the art to better understand the technical solutions of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.

[0023] This invention provides a red mud geopolymer stable, uniform, and dense mixture, which, by mass parts, comprises: 78-91 parts of natural aggregate, 9-22 parts of artificial lightweight aggregate, and 9-15 parts of red mud geopolymer. The artificial lightweight aggregate, by weight, includes: 60-70 parts red mud, 12-16 parts slag, 1-3 parts fly ash, 2-4 parts activator powder, and 16-23 parts water. The red mud geopolymer comprises, by weight parts: 52-62 parts red mud, 42-52 parts slag, 8-12 parts fly ash, 12-16 parts activator powder, and 40-50 parts water.

[0024] Specifically, the artificial lightweight aggregate has the following technical standards: water absorption rate of 8.8% and bulk density of 1003 kg / m³. 3 The cylinder compressive strength is 7.97 MPa.

[0025] Specifically, the red mud geopolymer has the following characteristics: initial setting time of 3.8h, final setting time of 6.2h, and 28-day compressive strength of 35.8MPa.

[0026] Secondly, the present invention provides a design method for a red mud geopolymer-stabilized, uniform, and dense mixture as described above, the design steps of which are as follows: S1. Weigh out the geopolymer powder, alkali activator powder and water according to the mass composition, prepare the alkali activator solution, mix the geopolymer powder and add the alkali activator and stir evenly, extrude and mold, sieve, and then allow to stand at room temperature for hydration and subsequent curing in a curing box to obtain artificial lightweight aggregate. S2. Weigh out the geopolymer powder, alkali activator powder and water according to the mass composition, prepare the alkali activator solution, mix the geopolymer powder and add the alkali activator, and then stir at low and high speeds until uniform to obtain the red mud geopolymer. S3. Weigh the artificial lightweight aggregate, natural crushed stone and red mud geopolymer according to the mass composition, mix the artificial lightweight aggregate, natural crushed stone and red mud geopolymer evenly to obtain a stable, uniform and dense red mud geopolymer mixture.

[0027] Specifically, in S3, the relationship between the mass fractions of the artificial lightweight aggregate and the red mud geopolymer is determined as follows: S31. Conduct compaction tests on red mud geopolymer-stabilized, uniform, and dense mixtures to determine the maximum dry density ρ under different amounts of artificial lightweight aggregate and geopolymer content. ij With optimum moisture content w ij ; S32, at the maximum dry density ρ ij With optimum moisture content w ij Under these conditions, cylindrical specimens are formed and cured to the specified age. The 7-day unconfined compressive strength and 7-day splitting strength are tested to determine the geopolymer content and artificial lightweight aggregate content of the red mud geopolymer stable, uniform, and dense mixture that meet the strength standard requirements.

[0028] Specifically, in S32, the steps for determining the 7d unconfined compressive strength and the 7d splitting strength are as follows: S321. The pavement structure and calculation conditions are proposed. The elastic modulus of the red mud geopolymer stable uniform dense base course under different working conditions is adopted by formula (1). in, denoted as t, where 4183 is the elastic modulus of the base material at age t, and 4183 is the empirical coefficient obtained from regression fitting. For the fitting formula, t represents the age; stress calculation software was used to calculate the tensile stress at the bottom of the red mud geopolymer stable uniform dense base course under different working conditions. ; S322. Assuming the flexural tensile strength [s] of the red mud polymer-stabilized uniform and dense base course, the fatigue damage of the red mud polymer-stabilized uniform and dense base course under different working conditions is calculated using formula (2). D i Then, the cumulative fatigue damage D is calculated using formula (3); Among them, D p For the first p Fatigue damage values ​​under various working conditions; n p For the first p The actual number of times it is used under various working conditions For the first p The number of fatigue cycles that a material can withstand under a certain working condition usually refers to the number of times the vehicle load or axle load is applied under that working condition. S323. When the cumulative fatigue damage is 0.95~1.0, [s] is accepted as the flexural strength standard; otherwise, [s] is adjusted and step 3.2 is repeated until the cumulative fatigue damage meets the requirements. S324. Calculate the 7d flexural strength standard [s7] using formula (4) from [s]. Wherein, 0.82 is the reference strength coefficient, which is usually obtained by experimental fitting; To fit the empirical formula; S325. Using formula (5), calculate the 7d splitting strength standard [R] from [s7]. t ], using formula (6) from [R t Calculate the standard 7-day unconfined compressive strength [R] c ] .

[0029] Specifically, in S32, the mass percentages of the geopolymer content and the artificial lightweight aggregate content are as follows; When the mass content of the artificial lightweight aggregate is 9-13%, the mass content of the red mud geopolymer is 9-11%, and the remainder is natural aggregate; When the mass content of the artificial lightweight aggregate is 13-17%, the mass content of the red mud geopolymer is 11-13%, and the remainder is natural aggregate; When the mass content of the artificial lightweight aggregate is 17-22%, the mass content of the red mud geopolymer is 13-15%, and the remainder is natural aggregate.

[0030] To demonstrate the effectiveness of the present invention, the following embodiments are provided for verification.

[0031] Example 1 See Figure 1 As shown, this embodiment provides a red mud geopolymer stable, uniform, and dense mixture, comprising the following components in parts by weight: 87-91 parts of natural aggregate, 9-13 parts of artificial lightweight aggregate, and 9-11 parts of red mud geopolymer.

[0032] A strength design standard for a red mud geopolymer-stabilized, uniform, and dense base course is established according to the following steps: S1. The pavement structure of the secondary highway is proposed as shown in Table 1. The elastic modulus under different working conditions is calculated according to formula (1), and the calculation results are shown in Table 2.

[0033] Table 1. Pavement Structure of Secondary Highways Table 2 Elastic modulus under different working conditions Stress calculation software was used to calculate the tensile stress at the bottom of the red mud geopolymer stable uniform dense base course under different working conditions. The calculation results are shown in Table 3.

[0034] Table 3 Calculated values ​​of tensile stress at the bottom of the subbase under different working conditions S2. Assuming the flexural tensile strength [s] of the red mud polymer-stabilized uniform and dense base course, the fatigue damage of the red mud polymer-stabilized uniform and dense base course under different working conditions is calculated using formula (2). Then, the cumulative fatigue damage D is calculated using formula (3), and the calculation results are shown in Table 4.

[0035] Table 4. Cumulative fatigue damage structure of road structures under various working conditions S3, the cumulative fatigue damage is 0.965, and [s]=0.62 is accepted as the standard for bending tensile strength.

[0036] S4. Using formula (4), the standard 7-day flexural strength [s7] of the red mud geopolymer stable uniform dense base course is calculated to be 0.50 MPa based on [s] = 0.62.

[0037] S5. Using formula (5), calculate the 7d splitting strength standard [R] from [s7]. t ] = 0.36MPa, using formula (6) from [R t Calculate the standard 7-day unconfined compressive strength [R] c =3.94MPa.

[0038] This embodiment provides a design method for a polymer-stabilized, uniform, and dense mixture of red mud, which is carried out according to the following steps: S1. Weigh 65 parts red mud, 14 parts slag, 2 parts fly ash, 3 parts activator powder, and 19 parts water according to the mass composition. Prepare an alkaline activator solution, mix the aggregate powder (red mud, fly ash, and slag powder), add the alkaline activator, and stir evenly. After forming by an extrusion granulator, pass through a 4.75mm sieve, and then allow it to stand at room temperature for 1 day for hydration and subsequently cure in a curing box for 7 days to prepare artificial lightweight aggregate. The activator powder is a composite system of sodium hydroxide and sodium silicate, and the modulus of the composite activator is 1.2.

[0039] S2. Weigh out 52 parts red mud, 42 parts slag, 10 parts fly ash, 14 parts activator powder, and 45 parts water according to the mass composition. Prepare an alkaline activator solution, mix the geopolymer powder (red mud, fly ash, and slag powder), add the alkaline activator, stir at low speed for 30 seconds, then stir at high speed for 3 minutes until uniform, and prepare red mud geopolymer.

[0040] S3. Weigh out 9-13 parts of artificial lightweight aggregate, 87-91 parts of natural crushed stone, and 9-11 parts of red mud geopolymer according to the mass composition. Mix the artificial lightweight aggregate, natural crushed stone, and red mud geopolymer evenly to obtain a stable, uniform, and dense red mud geopolymer mixture.

[0041] S4. Conduct compaction tests on the red mud geopolymer-stabilized, uniform, and dense mixture to determine the maximum dry density ρ under different amounts of artificial lightweight aggregate and geopolymer. ij With optimum moisture content w ij The experimental results are shown in Table 5.

[0042] Table 5. Compaction test results of red mud geopolymer-stabilized homogeneous and dense mixture. S5, at the maximum dry density ρ ij With optimum moisture content w ij Below, cylindrical specimens with a diameter of φ150mm×150mm were formed and cured to the specified age. The 7-day unconfined compressive strength and 7-day splitting strength of the red mud geopolymer stable uniform dense mixture were tested. The test results are shown in Table 6.

[0043] Table 6. Test results of strength of polymer-stabilized, homogeneous, and dense mixture of red mud. Using the design method of Example 1, the red mud geopolymer-stabilized, uniform, and dense mixture was designed. The actual test results of the 7-day unconfined compressive strength and 7-day splitting strength were better than the theoretical calculation values. Therefore, according to the strength design standard, when the mass content of artificial lightweight aggregate in the red mud geopolymer-stabilized, uniform, and dense mixture is 9-13%, the red mud geopolymer content that meets the strength requirements is 9-11%.

[0044] Example 2 This embodiment provides a red mud geopolymer-stabilized, uniform, and dense mixture, comprising the following components in parts by weight: 83-87 parts of natural aggregate, 13-17 parts of artificial lightweight aggregate, and 11-13 parts of geopolymer.

[0045] A strength design standard for a red mud geopolymer-stabilized, uniform, and dense base course is established according to the following steps: S1. The pavement structure of the high-grade highway is proposed, as shown in Table 7. The elastic modulus under different working conditions is calculated according to formula (1), and the calculation results are shown in Table 8.

[0046] Table 7. Pavement Structure of High-Grade Highways Table 8 Elastic modulus under different working conditions The tensile stress at the bottom of the red mud geopolymer stable uniform dense base course under different working conditions was calculated using stress calculation software. The calculation results are shown in Table 9.

[0047] Table 9 Calculated values ​​of tensile stress at the bottom of the subbase under different working conditions S2. Assuming the flexural tensile strength [s] of the red mud polymer-stabilized uniform and dense base course, the fatigue damage of the red mud polymer-stabilized uniform and dense base course under different working conditions is calculated using formula (2). Then, the cumulative fatigue damage D is calculated using formula (3), and the calculation results are shown in Table 10.

[0048] Table 10 Cumulative fatigue damage structure of road structures under various working conditions S3, with a cumulative fatigue damage of 0.975, is accepted as the flexural strength standard with [s]=0.67.

[0049] S4. Using formula (4), the standard 7-day flexural strength [s7] of the red mud geopolymer stable uniform dense base course is calculated to be 0.54 MPa based on [s] = 0.67.

[0050] S5. Using formula (5), calculate the 7d splitting strength standard [R] from [s7]. t ] = 0.39MPa, using formula (6) from [R t Calculate the standard 7-day unconfined compressive strength [R] c =4.21MPa.

[0051] This embodiment provides a design method for a polymer-stabilized, uniform, and dense mixture of red mud, which is carried out according to the following steps: S1. Weigh 65 parts red mud, 14 parts slag, 2 parts fly ash, 3 parts activator powder, and 19 parts water according to the mass composition. Prepare an alkaline activator solution, mix the aggregate powder (red mud, fly ash, and slag powder), add the alkaline activator, and stir evenly. After forming by an extrusion granulator, pass through a 4.75mm sieve, and then allow it to stand at room temperature for 1 day for hydration and subsequently cure in a curing box for 7 days to prepare artificial lightweight aggregate. The activator powder is a composite system of sodium hydroxide and sodium silicate, and the modulus of the composite activator is 1.3.

[0052] S2. Weigh out 57 parts red mud, 46 parts slag, 10 parts fly ash, 14 parts activator powder, and 45 parts water by mass. Prepare an alkaline activator solution. Mix the geopolymer powder (red mud, fly ash, and slag powder) and add the alkaline activator. Stir at low speed for 30 seconds and then at high speed for 3 minutes until uniform. Prepare red mud geopolymer.

[0053] S3. Weigh 83-87 parts of natural aggregate, 13-17 parts of artificial lightweight aggregate, and 11-13 parts of geopolymer according to the mass composition. Mix the artificial lightweight aggregate, natural crushed stone, and red mud geopolymer evenly to obtain a stable, uniform, and dense red mud geopolymer mixture.

[0054] S4. Conduct compaction tests on the red mud geopolymer-stabilized, uniform, and dense mixture to determine the maximum dry density ρ under different amounts of artificial lightweight aggregate and geopolymer. ij With optimum moisture content w ij The experimental results are shown in Table 11.

[0055] Table 11 Compaction test results of polymer-stabilized, homogeneous, and dense mixtures made from red mud. S5, at the maximum dry density ρ ij With optimum moisture content w ijBelow, cylindrical specimens with a diameter of φ150mm×150mm were formed and cured to the specified age. The 7-day unconfined compressive strength and 7-day splitting strength of the red mud geopolymer stable uniform dense mixture were tested. The test results are shown in Table 12.

[0056] Table 12 Test Results of Strength of Polymer-Stable, Homogeneous, and Dense Red Mud Mixture Using the design method of Example 2, the red mud geopolymer-stabilized, uniform, and dense mixture was designed. The actual test results of the 7-day unconfined compressive strength and 7-day splitting strength were better than the theoretical calculation values. Therefore, according to the strength design standard, when the mass content of artificial lightweight aggregate in the red mud geopolymer-stabilized, uniform, and dense mixture is 13-17%, the red mud geopolymer content that meets the strength requirements is 11-13%.

[0057] In summary, the red mud geopolymer stable, uniform, and dense mixture designed using the design method of this invention meets the application requirements in road engineering.

[0058] It should be noted that the activator is an alkaline activator, which is a type of chemical substance that can activate the potential activity of commonly used industrial waste residues such as slag and fly ash.

[0059] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention.

[0060] It should be understood that the present invention is not limited to the content already described above, and various modifications and changes can be made without departing from its scope. The scope of the present invention is limited only by the appended claims.

Claims

1. A red mud geopolymer-stabilized, uniform, and dense mixture, characterized in that, Based on mass fractions, it includes: 78-91 parts natural aggregate, 9-22 parts artificial lightweight aggregate, and 9-15 parts red mud geopolymer. The artificial lightweight aggregate, by weight, includes: 60-70 parts red mud, 12-16 parts slag, 1-3 parts fly ash, 2-4 parts activator powder, and 16-23 parts water. The red mud geopolymer comprises, by weight parts: 52-62 parts red mud, 42-52 parts slag, 8-12 parts fly ash, 12-16 parts activator powder, and 40-50 parts water.

2. The red mud geopolymer-stabilized, uniform, and dense mixture according to claim 1, characterized in that, The particle size distribution of the natural aggregate and the artificial lightweight aggregate, according to the mass percentage, is as follows: 9-22% artificial lightweight aggregate (5-10mm), 32-48% natural aggregate (5-10mm), 15-16% natural aggregate (3-5mm), and 28-30% natural aggregate (0-3mm).

3. The red mud geopolymer-stabilized, uniform, and dense mixture according to claim 1, characterized in that, The artificial lightweight aggregate has the following technical standards: water absorption rate of 8.8~10.0% and bulk density of 1003~1043 kg / m³. 3 The compressive strength of the cylinder is 7.31~8.51MPa.

4. The red mud geopolymer-stabilized, uniform, and dense mixture according to claim 1, characterized in that, The red mud geopolymer has the following characteristics: initial setting time of 3.8~4.1h, final setting time of 6.2~6.6h, and 28-day compressive strength of 35.8~36.3MPa.

5. A design method for a red mud geopolymer-stabilized, uniform, and dense mixture based on any one of claims 1 to 4, characterized in that, The design steps are as follows: S1. Weigh out the geopolymer powder, alkali activator powder and water according to the mass composition, prepare the alkali activator solution, mix the geopolymer powder and add the alkali activator and stir evenly, extrude and mold, sieve, and then allow to stand at room temperature for hydration and subsequent curing in a curing box to obtain artificial lightweight aggregate. S2. Weigh out the geopolymer powder, alkali activator powder and water according to the mass composition, prepare the alkali activator solution, mix the geopolymer powder and add the alkali activator, and then stir at low and high speeds until uniform to obtain the red mud geopolymer. S3. Weigh the artificial lightweight aggregate, natural crushed stone and red mud geopolymer according to the mass composition, mix the artificial lightweight aggregate, natural crushed stone and red mud geopolymer evenly to obtain a stable, uniform and dense red mud geopolymer mixture.

6. The design method according to claim 5, characterized in that, In S3, the relationship between the mass fractions of the artificial lightweight aggregate and the red mud geopolymer is determined as follows: S31. Conduct compaction tests on red mud geopolymer-stabilized, uniform, and dense mixtures to determine the maximum dry density ρ under different amounts of artificial lightweight aggregate and geopolymer content. ij With optimum moisture content w ij ; S32, at the maximum dry density ρ ij With optimum moisture content w ij Under these conditions, cylindrical specimens are formed and cured to the specified age. The 7-day unconfined compressive strength and 7-day splitting strength are tested to determine the geopolymer content and artificial lightweight aggregate content of the red mud geopolymer stable, uniform, and dense mixture that meet the strength standard requirements.

7. The design method according to claim 6, characterized in that, In S32, the steps for determining the 7d unconfined compressive strength and the 7d splitting strength are as follows: S321. The pavement structure and calculation conditions are proposed. The elastic modulus of the red mud geopolymer stable uniform dense base course under different working conditions is adopted by formula (1). in, denoted as t, where 4183 is the elastic modulus of the base material at age t, and 4183 is the empirical coefficient obtained from regression fitting. For the fitting formula, t represents the age; stress calculation software was used to calculate the tensile stress at the bottom of the red mud geopolymer stable uniform dense base course under different working conditions. ; S322. Assuming the flexural tensile strength [s] of the red mud polymer-stabilized uniform and dense base course, the fatigue damage of the red mud polymer-stabilized uniform and dense base course under different working conditions is calculated using formula (2). D p Then, the cumulative fatigue damage is calculated using formula (3). D ; Among them, D p For the first p Fatigue damage values ​​under various working conditions; n p For the first p The actual number of times it was used under various working conditions For the first p The number of fatigue cycles that a material can withstand under a certain working condition usually refers to the number of times the vehicle load or axle load is applied under that working condition. S323. When the cumulative fatigue damage is 0.95~1.0, [s] is accepted as the flexural strength standard; otherwise, [s] is adjusted and step 3.2 is repeated until the cumulative fatigue damage meets the requirements. S324. Calculate the 7d flexural strength standard [s7] from [s] using formula (4); Wherein, 0.82 is the reference strength coefficient, which is usually obtained by experimental fitting; To fit the empirical formula; S325. Using formula (5), calculate the 7d splitting strength standard [R] from [s7]. t ], using formula (6) from [R t Calculate the standard 7-day unconfined compressive strength [R] c ]: 。 8. The design method according to claim 6, characterized in that, In S32, the mass percentages of the geopolymer content and the artificial lightweight aggregate content are as follows; When the content of the artificial lightweight aggregate is 9-13%, the content of the red mud geopolymer is 9-11%, and the remainder is natural aggregate; When the mass content of the artificial lightweight aggregate is 13-17%, the mass content of the red mud geopolymer is 11-13%, and the remainder is natural aggregate; When the mass content of the artificial lightweight aggregate is 17-22%, the mass content of the red mud geopolymer is 13-15%, and the remainder is natural aggregate.

9. The application of the red mud geopolymer-stabilized, uniform, and dense mixture based on any one of claims 1 to 4, or the red mud geopolymer-stabilized, uniform, and dense mixture prepared based on any one of claims 5 to 8, in road engineering.